Моделювання процесів релаксаційної оптики в арсеніді індію - Трохимчук, Петро; Петрович, Діана; Березюк, Геннадій; Пеньковський, Михайло; Trokhimchuck, Petro; Petrovych, Diana; Berezyuk, Gennadiy; Pen’kovskiy, Mychaylo (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Наведено результати моделювання ефектів релаксаційної оптики в арсеніді індію на прикладі взаємодії імпульсного випромінювання рубінового лазера з арсенідом індію. Для моделювання вибран о дводифузійну модель та фізико-хімічну модель каскадного збудження відповідного типу хімічних зв’язків в режимі насичення збудження. Також обговорено питання про фізико-хімічні аспекти інтерференційних явищ. ; Results of modeling of effects of relaxed oрtics on example of pulse Rubylaser radiation with indium arsenide are represented. Two -diffusive model and physical-chemical model of cascade excitation of proper chemical bonds in regime of saturation of excitation were used. Questions of physical -chemical aspects of interference phenomena are discussed too. Modeling was realized for profiles of distribution of laser generated donor centers with help of measurement Hall effect with layerwise bleeding of irradiated layers and method of Rutherford backscatterind spectra of protons with energy 500 keV. Questions of physical-chemical aspects of interference phenomena are discussed too. Estimations of t hreshold of initiation of interference phenomena for laser irradiatin are represented too.
Modeling of Processes of Relaxed Optics in Indium Arsenide
Keywords: релаксаційна оптика; арсенід індію; relaxed optics; indium arsenide